Islamic leadership as a mechanism to achieve Sustainable competitive advantage in small and medium enterprises A case study of small and medium enterprises in the private industrial sector in Jijel Province - Algeria - hamimdat, Saleh; Slaimi, Ahmed (Dirassat Journal Economic Issue, 2016)
This article studies the subject of Islamic leadership as a mechanism to achieve ongoing competitive advantage in SMEs, despite the fact that the Islamic leadership was applied in the military field or in state affairs conduct, however, our analysis of the merits and qualities of leaders where, especially Holy Prophet and his successors we found that it can be drop all this on the leaders of companies, and that this type of leadership that integrates all the occidental positives leadership styles and get rid of its negatives and that is what is part of the scientific miracles of the Holy Quran and the Sunnah, which benefited them almost all fields such as medicine, astronomy, biology and other while we find that it is null in the management area, this study is trying to determine the ability of this type of leadership in achieving a sustainable competitive advantage for SMEs in the private industrial sector in County of Jijel, especially that the most of the small and medium enterprises do not live too much as a result of their inability to compete and keep up with environment developments.